(untitled) (Fiep Bulletin - online, 2014)
This article aims at identifying and assessing the Scandinavian influence on FIEP, from its creation to the present, but more specifically during the time called "Swedish period" from 1930 to 1958. For that purpose, an intense documental and bibliographical investigation was carried out. That research enabled the recollection of important personalities in those days, whose influence has remained until now, such as Per Henrik Ling and Major J.G. Thulin. The main hypothesis is that the evolution of Ling’s gymnastics under J.G. Thulin’s influence and many other distinguished Scandinavian Physical Education professors was clearly reflected in the development of the Federation and its huge impact through the organization of many great events, courses, conferences and the expansion of "Neo-Swedish gymnastics" all over the world. At first we shall analyze the Scandinavian influence on FIEP from the cultural-historical point of view, including the influence on the accomplishments in the period and the creation and development of FIEP Bulletin. After that, we shall make a report of the studies and scientific researches developed, the creation of the Thulin Prize and the traits of his personality. At last, we shall present a research paper about the assessment of the longitudinal effects of the "Modern Finnish Feminine Gymnastics".